Potential causal associations of PM2.5 and osteoporosis: a two-sample mendelian randomization study - Zhang, Yi; Yu, Jinsheng; Pei, Hang; Zhao, Xinzheng; Wang, Chao; Wang, Guanyin; Shen, Zan; Hua, Jiang; He, Bangjian (Frontiers in Genetics, 2024)
Background: Observational studies suggest a potential association between atmospheric particulate matter 2.5 (PM2.5) and osteoporosis, but a causal association is unclear due to the presence of confounding factors.We utilized bone mineral density (BMD) indices at four specific sites to represent osteoporosis: femoral neck (FN-BMD), lumbar spine (LS-BMD), forearm (FA-BMD), and heel (HE-BMD). The PM2.5 data was obtained from the UK Biobank database, while the datasets for FN-BMD, LS-BMD, and FA-BMD were obtained from the GEFOS database, and the dataset for HE-BMD was obtained from the EBI database. A two-sample Mendelian randomization analysis was conducted using mainly the inverse variance weighted (IVW) method, horizontal pleiotropy and heterogeneity were also assessed.The results indicated that PM2.5 was not correlated with a decrease in FN-BMD (β:-0.305, 95%CI: -0.762, 0.153), LS-BMD (β: 0.134, 95%CI: -0.396, 0.666), FA-BMD (β: -0.056, 95%CI: -1.172,1.060), and HE-BMD (β: -0.084, 95%CI: -0.261,0.093). Additionally, acceptable levels of horizontal pleiotropy and heterogeneity were observed.In contrast to most observational studies, our research did not discover a potential causal relationship between PM2.5 and the development of osteoporosis.